Preliminary studies: differences in microRNA expression in asthma and chronic obstructive pulmonary disease - Pietrusińska, Małgorzata; Pająk, Aneta; Górski, Paweł; Kuna, Piotr; Szemraj, Janusz; Goździńska-Nielepkowicz, Agnieszka; Pietras, Tadeusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : The asthma- and chronic obstructive pulmonary disease (COPD)-related morbidity has been increasing during the recent years. Both asthma and COPD are diseases of inflammatory etiology. The increasing interest in the pathomechanisms involved in the development of obstructive pulmonary diseases seems to be fully justified. Recent research has attempted to determine the associations of microRNA with the pathogenesis of pulmonary diseases. Aim : To assess the expression of microRNA in the blood sera of patients diagnosed with bronchial asthma and chronic obstructive pulmonary disease in comparison with healthy subjects. Material and methods : In our study, at the preliminary stage, we compared the expression of miRNA in the groups of patients with asthma and COPD versus the control group of healthy subjects. Results : A significant difference in hsa-miRNA-224, hsa-miRNA-339-5p, hsa-miRNA-382 in patients with asthma and COPD as compared with the controls was noted. Conclusions : With such difference of expression of specific micro-RNA in serum of patient with asthma and COPD, those small non-coding RNA has to play a significant role in those diseases pathway. Therefore we expect to increase the size and differentation of the study groups in next studies.